Temporal and spatial distribution of the alpine meadow carbon budget in Gannan, China from 1969 to 2018 - Wang, Xingyu; Zhang, Meiling; Nazieh, Stephen; Nkrumah, Teddy (Frontiers in Environmental Science, 2023)
In recent years, carbon balance has been a hot research topic both at home and abroad. The grasslands are rich in carbon storage and are also sensitive to climate change, and the Gannan alpine meadow, a distinct type of grassland in Gansu Province, is used as the study area in this paper. The consequences of climate change have a huge impact on human development and can even cause major human disasters. Effective management of climate change is, therefore, a major problem that currently needs to be solved, and grasslands play an indispensable role in the process of carbon deposition in terrestrial ecosystems. The CENTURY model has been used to study the spatial distribution and changes in the carbon budget in the Gannan alpine meadow of Gansu Province over the last 50 years, which is of great significance for climate change management. The results show that 1) the carbon budget has different distribution characteristics in different regions. 2) The spatial distribution of the carbon budget changes over time, as evidenced by the different spatial distribution of the carbon budget in each study stage and quarter. The spatial distribution differs as well. Some areas in the northern part of southern Gansu are carbon sources in spring and carbon sinks in summer, autumn, and winter. The spatial distribution of the carbon budget changes over time and is different at each stage, but it is a carbon sink overall. 3) The Gannan alpine meadow as a whole demonstrated a carbon sink phenomenon from 1969 to 2018, and the carbon balance is a carbon sink. 4) Every year, the carbon sink initially increases and then shows a decreasing trend, with the carbon sink reaching a maximum in August. 5) Temperature and precipitation are positively correlated with net ecosystem productivity (NEP). 6) In the last 50 years, the Gannan alpine meadow has sequestered 43,580.9 gC of carbon. The annual and monthly average NEP values are approximately 871.62 gC/m2 and 72.635 gC/m2, respectively.